Communiquer avec la nature pour apprendre sa culture : Le rôle de l’iconicité sonore animale dans la communication orale de l’enfant (Maroc/Pérou) - Simenel, Romain (Anthropologica, 2018)
In the perspective of questioning the links between cultural transmission and experience of nature, this article proposes to analyze the impact of animal sound iconicity on the development of communicative ability of children and the elaboration of their first knowledge and representations of the world. In different contexts, one from ordinary life, the other from ritual, two cases, the one of Aït Ba’amran tribes in South Morocco and the one of Quechua populations of Peruvian Amazonia, show that the imitation of animal sounds can be used as a first framework for oral communication development between adults and babies and for the transmission of world compositions. The main advantage of comparing the Moroccan and the Amazonian examples is to clarify the mechanism that enable to the analogue experience of the interpretative herd’s driving in one case and the animistic experience of hunting with lure in the other case, to resonate in the cultural learning of the child from a very young age.